An intelligent approach of analyzing noise in media communication using noise theory - Yiming Zhang; Ya Lin Shi; Che Ching Lai (Suleyman Demirel University, 2025)
In order to create a positive impression of a city, one can use social media platforms and noise theory to strategically manage the flow of information. This will make sure that the important messages with the city are heard and understood, even with all the online content out there. The city's marketing message may easily be lost in the sea of information that is social media. According to noise theory, this is why it's so important to create material that stands out from the crowd. This research takes a look at how the official "Xi'an Release" platforms of the Xi'an government's new media department spreads the city's image and how new media works in general. In order to address these issues, this study employs quantitative research methodologies to examine the audience, content, along with channels via the examination of 3,357 pieces released on Xi'an governmental social media accounts, as well as the statistical data collected from 384 respondents. There is a positive correlation between the audience's perception of public opinion noise on Xi'an municipally owned media platforms and their satisfaction with Xi'an's city image, as well as with their needs and satisfaction for content, socialization, while entertainment on these platforms. In terms of how they affect audience satisfaction, information demands are at the top, subsequent to social and entertainment requirements. Noise theory is used to deal with comments from the general public. In addition, from this, unique strategies are proposed. The theoretical underpinnings and citations of research data in this work have practical applications for improving Xi'an's productivity, attractiveness, development, while vitality via the control and dissemination of the city's public perception.